Isorhapontigenin, a potential anti-AD natural product targeting multiple pathways, discovered via network proximity and gene enrichment analyses - Pengfei Guo; Jun Zhao; Baoyue Zhang; Chao Wang; Yiming Bai; Ailin Liu (Phytomedicine Plus)
Background: Alzheimer's disease (AD) is a chronic, progressive neurodegenerative disorder of the brain characterized by an uncertain etiology and complex pathogenesis. Effective therapeutics remain urgently needed. Natural products (NPs) show significant potential in preventing/treating neurodegenerative diseases. Methods: In this study, the network proximity method (NPM) identified the NP Lg0005 (p = 0.05, z = -3.11) with potential anti-AD activity. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses elucidated its anti-AD mechanism of action (MOA). Neuroprotective effects were validated using D-galactose (D-gal)-induced AD rat models and SH-SY5Y cells. Results: KEGG analysis revealed Lg0005 primarily acts via AD, oxidative phosphorylation, apoptosis, and TNF signaling pathways, etc. GO analysis indicated it targets mitochondrial electron transport, mitochondrial components, and oxidoreductase activities, etc. Molecular docking and in vitro/in vivo experiments confirmed Lg0005 inhibited microglia/astrocyte activation, reducing TNF-α and IL-1β release. In addition, it alleviated oxidative damage by decreasing MDA and increasing catalase, ameliorated mitochondrial ultrastructural damage, and increased both Nissl body count and synaptic density in the hippocampal DG region, with efficacy comparable to β-nicotinamide mononucleotide (NMN) and donepezil. In summary, Lg0005 significantly improved cognitive function in AD models by reducing oxidative stress, suppressing neuroinflammation, and protecting mitochondrial and neuronal integrity. Conclusions: Integrating NPM, network pharmacology, and experimental validation, this study identified Lg0005 as a novel anti-AD candidate, offering a new strategy for neurodegenerative disease therapeutics.